Internet-based tapering of oral corticosteroids in severe asthma: a pragmatic randomised controlled trial. Issue 6 (7th April 2011) - Hashimoto, Simone; Brinke, Anneke Ten; Roldaan, Albert C; van Veen, Ilonka H; Möller, Gertrude M; Sont, Jacob K; Weersink, Els J M; van der Zee, Jaring S; Braunstahl, Gert-Jan; Zwinderman, Aeilko H; Sterk, Peter J; Bel, Elisabeth H
Abstract : Background: In patients with prednisone-dependent asthma the dose of oral corticosteroids should be adjusted to the lowest possible level to reduce long-term adverse effects. However, the optimal strategy for tapering oral corticosteroids is unknown. Objective: To investigate whether an internet-based management tool including home monitoring of symptoms, lung function and fraction of exhaled nitric oxide (FENO ) facilitates tapering of oral corticosteroids and leads to reduction of corticosteroid consumption without worsening asthma control or asthma-related quality of life. Methods: In a 6-month pragmatic randomised prospective multicentre study, 95 adults with prednisone-dependent asthma from six pulmonary outpatient clinics were allocated to two tapering strategies: according to conventional treatment (n=43) or guided by a novel internet-based monitoring system (internet strategy) (n=52). Primary outcomes were cumulative sparing of prednisone, asthma control and asthma-related quality of life. Secondary outcomes were forced expiratory volume in 1 s (FEV1 ), exacerbations, hospitalisations and patient's satisfaction with the tapering strategy. Results: Median cumulative sparing of prednisone was 205 (25–75th percentile −221 to 777) mg in the internet strategy group compared with 0 (−497 to 282) mg in the conventional treatment group (p=0.02). Changes in prednisone dose (mixed effect regression model) from baseline were −4.79 mg/day and +1.59 mg/day, respectively (p<0.001). Asthma control, asthma-related quality of life, FEV1, exacerbations, hospitalisations and satisfaction with the strategy were not different between groups. Conclusions: An internet-based management tool including home monitoring of symptoms, lung function and FENO in severe asthma is superior to conventional treatment in reducing total corticosteroid consumption without compromising asthma control or asthma-related quality of life. Clinical trial registration number: Clinical trial registered with http://www.trialregister.nl (Netherlands Trial Register number 1146).